Triterpene saponins from Silene gallica collected in North-Eastern Algeria. (April 2020) - Bechkri, Sara; Alabdul Magid, Abdulmagid; Sayagh, Charlotte; Berrehal, Djemaa; Harakat, Dominique; Voutquenne-Nazabadioko, Laurence; Kabouche, Zahia; Kabouche, Ahmed
Abstract: Eleven previously undescribed triterpene saponins, named silenegallisaponin A-K (1 –11 ), were isolated from the aerial parts of Silene gallica L. Their structures were elucidated by analysis of 1D and 2D-NMR spectroscopic data and mass spectrometry (HR-ESI-MS). The saponins comprised caulophyllogenin, echinocystic acid, or quillaic acid substituted at C-3 by a β -d -glucuronic acid or β -d -galactopyranosyl-(1 → 3)- β -d -glucuronopyranoside and at C-28 by a β -d -fucopyranose substituted at C-2 by a β -d -glucose and at C-3 by a β -d -glucose or a β -d -quinovose. Graphical abstract: Image 1 Highlights: Eleven undescribed triterpenoid saponins were isolated from Silene gallica L. Their structures were elucidated by 1D, 2D-NMR and HRESIMS analyses. A chemotaxonomic significance is given in the conclusion.